“Pasang”, Knowledge and Implementation of Local Wisdom in The Kajang Traditional Forest Area, South Sulawesi - Nurmala; Muh. Dassir; Supratman (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2022)
The Kajang tribe as a cultural and environmental tourism destination is a community of indigenous people who live in harmony with nature by having the life principle of "Kamase mase" (unpretentious) and are firm on the "Pasang" (message) of the ancestors. "Pasang" is a way of life for indigenous peoples originating from Turiek A'ra'na (the creator) which was passed down to Tu Mariolo (the first person). The core of "pasang", is to maintain and preserve the forest for a better life and more prosperous. The purpose of this research is to analyze the type of “pasang” as local knowledge and implementation of forest conservation in the Customary Areas. Data was collected through field observations and in-depth interviews with participants and key informants consisting of; 1) Customary Leaders, Ammatoa, 2) Customary Stakeholders, 3) Village Heads, 4) Non-Governmental Organizations, 5) indigenous peoples. The results showed that knowledge of local wisdom for forest conservation and management contained several "pasang". “Pasang” as Knowledge of local wisdom is implemented in the form of forest management zoning. The customary forest is divided into three zones; 1) core zone or sacred forest (borong karamaka or borong lompoa); 2) buffer zone, limited production forest (borong battasayya), and 3) utilization zone (borong Luarayya). The three forest zones have different functions and uses in Ammatoa supervision.